Optimasi Formula Pewarna Alami Berbasis Buah Naga Merah (Hylocereus polyrhizus) Afkir Hasil Foam-Mat Drying Dengan Metode Simplex Lattice Design (SLD) - Wiyono, Andi Eko; Amilia, Winda; Herlina, Herlina; Setiawan, Andrew; Aghata, Ola Riska Aprilia Intan; Savitri, Dewi Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Inferior red dragon fruit has the potential as a source of natural dye. This research aimed to examined the quality of natural dye powder as a referenced for optimization. To optimized the formula for natural dye powder based on rejected dragon fruit, and to examined the physical and chemical quality of natural dye powder at the optimum formula. The varied ingredients in this research were ascorbic acid and tween 80. The upper and lower limits of use of both ingredients were 3% and 1% for ascorbic acid, as well as 1% and 0.5% for tween 80. The method used laboratory experimental method and quantitative analysis data. The experimental design used in this research was an experiment with the application of the simplex lattice design (SLD) method, so that several formulas were obtained based on the variation of two factors. Results of the observation data were inputted into the Design-Expert version 13 application so that a regression equation is obtained to determine the optimum formula. All data were presented in tables and graphs and analyzed descriptively. The results showed that F5 (ascorbic acid 3%: tween 80 0.5%) was the optimum formula because it had the highest desirability of 0.998 with a water content of 2.15%; total dissolved solids 9.66%; pH 3.766; L 53.71, a 14.20; b 7.39; dissolved time 61.33 seconds; Chroma 16,00; Hue 27.33ᵒ (red), and anthocyanin content 3,37 mg/mL. On exposure to the sun, outdoor and indoor experienced the highest degradation, namely 30.48% and 0.93%, respectively.